IMPLEMENTASI KEBIJAKAN PENGUKURAN BIDANG TANAH PADA KANTOR PERTANAHAN KOTA PALU - Fahrul, Fahrul; Hasbullah, Hasbullah; Natsir, Nawawi (Katalogis, 2020)
The purpose of this study was to find out and analyze the implementation of the policy of measuring land parcels at The Palu City Land Office. This research is a qualitative method research with four informants selected. Data collection using observation, interview and documentation techniques. Data analysis techniques used are (1) Data Collection (2) Data Reduction (3) Data Pretentation (4) Data Verivication (5) Conclusion. Theory used in this study are Van Meter dan Van Horn theory that’s on (Subarsono, 2005), that’s theory measures policy implementation with: (1) Standards and targets (2) Resource (3) Comunication (4) Characteristics of implementing agents (5) Social, economic and political conditions (6) Disposition. Based on the results of research and analysis conducted by researchers, it can be concluded that the implementation of a land measurement measurement policy has not gone well. That’s can be described as follows: (1) The implementation of the policy of measuring land parcels in The Palu City Land Office is seen from the standard factors and the policy objectives have been going well. (2) The implementation of the Land Measuring policy at the Palu City Land Office as seen from the Resource factor has not gone well, this can be seen from inadequate facilities and infrastructure and the number of employees who are still lacking in the Palu City Land Office. (3) The implementation of the Land Measurements policy at the Palu City Land Office in terms of merit factors, characteristics, socio-economic and political conditions and disposition factors has not gone well, this can be seen from the inadequate facilities provided and supported by interviews with informants conducted at the research sites.